Konza - Richard Hansen (Oz, 1995)
Konza is a photographic record of a sculptural installation done in collaboration between Hansen and eleven students: Travis Bechtel, Dwayne Bondy, Karen Dunsford, Eric Goldstein, Joe Larsen, Curt Simmons, Susan Schultz, Robert Wheeler, Robert Whitman, Jim Wilson, Brian Yansen.